Politics and administrative practice in the Irish information society - Komito, Lee (Economic & Social Studies, 1997)
The Information Society is expected to transform political relations in industrial societies, but the extent to which transformations have already taken place is often underestimated. In the past, Irish politicians provided real or imagined patronage in exchange for the electoral support of citizens. The introduction of office information systems in the Irish civil service has lessened politicians' monopoly on administrative information. This increased public access to information has altered traditional politics in Ireland and enhanced democratic participation. However, any further changes should result from conscious policy decisions rather than as unplanned consequences of efficiency driven IT investments.
Keywords: Information society; Political participation; Information policy; Ireland